A comprehensive annotation dataset of intact LTR retrotransposons of 300 plant genomes - Shan-Shan Zhou (Nature Portfolio, 2021)
Measurement(s) LTR_retrotransposon • genome Technology Type(s) bioinformatics method • digital curation Factor Type(s) Species Sample Characteristic - Organism Rhodophyta • Chlorophyta • Bryophyta • Tracheophyta Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14684877